Prognostic value of left ventricular diastolic function and association with heart rate variability after a first acute myocardial infarction. Issue 4 (1st October 2001) - Poulsen, S H; Jensen, S E; Møller, J E; Egstrup, K
Abstract : OBJECTIVE: To study the prognostic value of left ventricular (LV) diastolic function and its relation with autonomic balance expressed by heart rate variability (HRV) in patients after a first acute myocardial infarction. DESIGN: The study population consisted of 64 consecutive patients with first acute myocardial infarction and 31 control subjects. Long and short term HRV indices were evaluated by 24 hour Holter monitoring, and LV systolic and diastolic function were assessed by two dimensional and Doppler echocardiography before discharge. Patients were divided into two groups: those with restrictive LV filling characteristics (deceleration time ⩽ 140 ms) and those with non-restrictive LV filling characteristics (deceleration time > 140 ms). RESULTS: Both long and short term HRV indices were significantly reduced in patients with restrictive LV filling compared with the non-restrictive group and control subjects. Mitral deceleration time and isovolumetric relaxation time correlated weakly but significantly with all indices of HRV whereas ejection fraction correlated weakly with the long term HRV indices. The mean follow up time was 14.9 (8.7) months. Multivariate analysis showed that mitral deceleration time (χ 2 = 6.4, p < 0.001) and ejection fraction ⩽ 40% (χ 2 = 4.4, p < 0.05) were independent predictors of cardiac death and readmission to hospital with congestive heart failure. CONCLUSIONS: A restrictive LV filling pattern was found to be the strongest predictor of adverse outcome independent of HRV and ejection fraction during follow up after a first acute myocardial infarction. Patients with restrictive LV filling characteristics had more reduced HRV than those with non-restrictive diastolic filling.